The role of China in the portuguese speaking african countries : The case of Mozambique - Ilhéu, Fernanda (2010)
Due to the Reform and Open Door Policies initiated in 1978, China recorded a fast sustainable economic growth with an estimated average GDP growth rate of 9.7% in the period of 1980-2008, turning China-- in 2009 - into the world's second largest economy, just after USA. With an export oriented economic model, highly supported by FDI, mostly from developed countries, China is, since 2002, the most attractive developing country for FDI flows, both at short and long terms, becoming not only the world's factory, but also its number one exporter, after surpassing Germany in 2009. With the biggest current account surplus balance, China has been able to achieve a foreign exchange reserve of US$ 2.2 trillion -- the world's largest reserve currency. Around 50% of this huge reserve is being applied in American bonds, while the remaining supports Chinese health and social security systems, Chinese banks' solvability, internationalization of the Chinese economy, investment in geostrategic positioning to guarantee energy independence and making foreign aid available to other developing countries. During 2008's global crisis, China was able to resist better than the major world economies even benefitting from this downturn to implement policies to reduce its economic imbalances. One of these imbalances is the gap between Chinese FDI and OFDI which is now progressively narrowing. In fact, in the near future, OFDI is expected even be larger than FDI. Mostly two types of Chinese OFDI can be distinguished: trade-oriented investment and resource-seeking investment. Governmental backing, including official developments assistance (ODA) has been crucial for the resource-seeking investment. Although the Chinese investment is nowadays more oriented to mature economies, its bulk is mainly directed to the other developing countries mainly to Latin American countries and now also to African countries. Following the Beijing Consensus, Chinese planners are pushing partnerships with African countries and within those, the Chinese government identified one strategic group worth to cooperate and invest, the Portuguese Speaking African Countries which are linked through a network of language and culture between themselves and also to other geostrategic economic spaces; to Europe via Portugal, to Latin America via Brazil and to Asia via Macau. These African countries have high expectations on the Chinese cooperation and our research questions are. (a) Should this investment be consider ODA or OFDI; (b) How far can Chinese finance flows contribute to the development of these countries in terms of employment, exports, technology transfer; (c) is this investment seen as an opportunity or a threat by local people, is it fulfilling the created expectations or not? In this paper our empirical case is researching the perception of Mozambique government on the ODA and OFDI Chinese investment there, and the conclusions were reached by analyzing the Mozambique government high officials opinions publically expressed or resulting from their answers to media inquires. We also will try to find secondary data with information on the perception of the population on China presence in Mozambique through secondary data.